Facies associations, sequence stratigraphy and timing of the earliest Jurassic peak transgression in central Spain (Iberian Range): Correlation with other Lower Jurassic sections - Cortés, J. E.; Gómez, J. J.; Goy, A. (Journal of Iberian Geology, 2009)
Facies associations and sequence stratigraphy of the Lower Jurassic shallow platform to peritidal carbonates of the Cuevas Labradas Formation (Sinemurian to Pliensbachian) have been studied in the Barranco de la Hoz section, located in the central−southern part of the Iberian Range. Four stratigraphical units (A to D) have been differentiated. Unit A, deposited in a restricted platform, is organized in aggradational thickening- and shallowing-upward sequences. Unit B, deposited in external restricted platform environments, is composed of shallowing- and deepening-upward sequences. This unit contains Polymorphites sp., Uptonia cf. jamesoni (SOW.) and Uptonia cf. angusta (QUENST.) that characterize the upper part of the Jamesoni Zone of the Lower Pliensbachian. The transgressive peak of 3rd order Cycle LJ2−2 is located in the marly facies of unit B. Unit C is composed of shallowing-upward sequences of “muddy” type in the lower part, deposited in the proximal part of the shallow restricted external platform and “grainy” type in the upper part, representing wave-dominated bioclastic shoals. Unit D is constituted by peritidal shallowing-upward sequences deposited in shallow restricted subtidal environment of the internal platform to the intertidal and supratidal environments. The 5th order cycles constituting the 3rd order facies Cycle LJ2−2, have been grouped into 4th order cycles. The duration of the 3rd order Cycle LJ2−2 is estimated as 2.6 Myr, and the possible average duration of the 4th order cycles as 0.4 Myr. This figure is close to the most frequent duration of the long-term Milankovitch orbital eccentricity cycles. Comparison of the obtained results with other Lower Jurassic sections in Spain, Europe and with the global cycles shows that the boundary between cycles LJ−1 and LJ−2, which represents the onset of the first Jurassic transgression and the peak transgression identified in this work at the Lower Pliensbachian Jamesoni Zone as well as the boundary between cycles LJ−2 and LJ−3 seem to represent good criteria for correlation between the different palaeogeographical domains.